Separation of gold(III) ions by 1,8-diaminonaphthalene-formaldehyde chelating polymer - Erim, Ümit Can; Gülfen, Mustafa; Aydın, Ali Osman (Elsevier Science Bv, 2013)
In the present work, a new 1,8-diaminonaphthalene-formaldehyde (1,8-DAN-F) polymer was synthesized by the reaction of 1,8-DAN with formaldehyde solution. The structure of 1,8-DAN-F polymer was characterized by elemental analysis, FT-IR spectroscopy and thermal analysis. In order to prepare a useful adsorbent, 1,8-DAN-F polymer was blended at the ratio of 25% with polyvinylchloride (PVC) using THF solvent. 1,8-DAN-F/PVC polymer blend was used in selective separation and recovery of Au(III) ions from Fe(III), Cu(II) and Ni(II) ions. The effects of pH and the initial concentration of Au(III) ions on the adsorption were examined by the batch technique. The optimum pH level was found to be 1 for the Au(III) adsorption. Furthermore, the adsorption data were applied to the Langmuir and Freundlich isotherms. It was found that the adsorption data fitted well to the Langmuir isotherm. The maximum Au(III) adsorption capacity (q(max)) of the polymer blend was 119.0 mg.g(-1). The adsorption kinetics indicated that the Au(III) adsorption proceeds according to the pseudo-second-order model. Also, the separation of Au(III) ions from Fe(III), Cu(II) and Ni(II) ions was examined by the column technique. The column studies showed that Au(III) ions can be separated and concentrated from the base metal ions.
WOS: 000318326900013
Keywords: Gold(III) Ions; 1,8-Diaminonephthalene Formaldehyde; Chelating Polymer; Adsorption; Separation